Mobile phone dependence and musculoskeletal pain prevalence in adolescents: a cross-sectional study - Parra-Fernandez, David Mauricio; Alfonso-Mora, Margareth Lorena; Sánchez-Vera, María Alejandra; Sarmiento-Gonzalez, Paola; García Becerra, Andrea Milena; Guerra-Balic, Miriam (Frontiers in Pain Research, 2025)
ObjectiveTo investigate the association between adolescents' mobile phone dependence (MPD) and musculoskeletal pain.MethodsA cross-sectional study was conducted among 622 adolescents aged 10–18 in Tabio, Colombia. Participants completed an online survey that included the MPD and the Nordic Musculoskeletal Questionnaire, which assessed musculoskeletal pain symptoms.Results56.3% (n = 350) participants reported experiencing musculoskeletal pain, with the upper back being the most affected area (30.4%, n = 193). Adolescents reporting pain had significantly higher MPD scores compared to those without pain (mean 29 vs. 24, p < 0.001). Additionally, females exhibited higher MPD scores than males (mean 29 vs. 25, p < 0.001) and had a higher prevalence of pain (32% vs. 24%). Furthermore, older adolescents in the 11th grade had higher MPD scores than younger adolescents in the 5th grade (mean 31 vs. 21, p < 0.019). Logistic regression analysis indicated that specific MPD dimensions, namely “abuse” and “difficulty regulating use,” were significantly associated with general pain and neck pain, but no association was observed with upper back pain. Furthermore, female sex was linked to both neck and upper back pain.ConclusionThis study found that the MPD dimensions of “abuse” and “difficulty regulating use” were significantly associated with neck pain, regardless of the adolescents' sex.